Comparison of heat capacity of solid explosives by DSC and group contribution methods - Pilař Radim; Pachmáň Jiří; Matyáš Robert; Honcová Pavla; Honc Daniel (Springer, 2015)
The isobaric heat capacities of solid explosive materials were measured using differential scanning calorimeter. The values of C-p were determined at temperature 298.15 K and compared to theoretical data calculated using the group additivity approach. Several group contribution methods were tested, showing that certain method for some explosives provides estimation of C-p with error only 1 %. Generally, the average error limit for calculated C-p was about 11 %, which is insufficient.
Porovnání tepelných kapacit výbušnin stanovených pomocí DSC a příspěvkovou metodou
Keywords: Explosive material; Isobaric heat capacity; Differential scanning calorimetry; Modified stepwise method; Group contribution method; výbušný materiál; izobarická tepelná kapacita; diferenciální skenovací kategorie; modifikovaná skoková metoda; příspěvková metoda